EXPERIENCE OF USING A NON-SELECTIVE BETA-BLOCKER IN COMPLEX THERAPY OF REPOLARIZATION DISORDERS IN YOUNG ATHLETES - A. Yu. Tikhomirov; O. V. Minyaeva; T. V. Tikhomirova (Исследования и практика в медицине)
Purpose. To study the effectiveness of various schemes of correction of repolarization disorder syndrome, including with the use of beta-blockers, in young athletes of the initial training group.Materials and methods. At the first stage, 410 children involved in sports sections were examined. The average age of the examined was 12.22 ± 3.11 years. At the second stage, the athletes (boys) of the initial training group were selected from the surveyed contingent, engaged in martial arts. The groups were formed: A – people with violation of myocardial repolarization processes (72 patients, the average age 10,50 ± 0,35 years), the control group – people without changes in an electrocardiogram (33 people, the average age 10.36 ± 0, 62 years old). All underwent an electrocardiographic study at rest and after physical activity on the Innomed HS80GL apparatus with analysis of the main indicators. The vegetative status and the state of adaptation were estimated by Kerdo index and adaptive potential by Baevsky. After the examination, the subgroup A1 (40 people) was prescribed metabolic and antioxidant drugs. Additionally, in the subgroup A2 (32 people), a non-selective beta-blocker was included in the treatment regimen. The course of treatment is 10 days. The analysis of indicators was carried out in 10 days and in a month after the initiation treatment. Statistical processing was carried out in the program Statistica.Results. An earlier disappearance of cardialgia was determined in the subgroup A2 (p < 0.05), whereas in the subgroup A1, 5% of patients had complaints not only at the end of the course, but also a month later after the initiation treatment. The more rapid positive dynamics of the electrocardiographic pattern with a more stable result was observed with the prescription of a beta-blocker.Conclusion. It was proved the advisability of prescribing of beta-blockers in the treatment of beginning athletes with violation of myocardial repolarization against sympathicotonia.